Program Pendampingan Budidaya Lobster Desa Keruak Kabupaten Lombok Timur - Wira Hendri; Mahfuzi, Syafira; Komala, Rina; Aprianto, Dedi; Aryani, R. Ayu Ida (Insan Kreasi Media, 2023)
Lobster is an important marine product for the people living at the coastal area in Keruak. Lobster has a high economic value, but it has not been managed optimally. In the development of lobster, lobster farmers have experienced a decline in production over the last few years due to various factors, nemely almost all fishermen living at the coastal area in Keruak village who are not lobster farmers. Lobster is only a partial/seasonal business. The coastal fishermen only have an ability to traditionally catch lobster seeds. However they do not have knowledge to cultivate lobster. Almost all lobster seeds caught at sea are sold to collectors so that the added value of this business is almost nothing. The community assistance program that was carried out by society service team in collaboration with local communities through a lobster cultivation in the coastal community tries to explain the problem. People can know and understand the types of lobsters that are suitable for cultivation in their area.s